Edukasi Kesehatan tentang Penggunaan Antibiotik secara Bijak pada Masyarakat Car Free Day Jakarta - Christian, Yulius Evan; Gunawan, Untung; Laurensia; Chaineyla, Florencia; Alwi, Felisca Emmalyn; Susanto, Sharon (Ilin Institute, 2025)
The misuse of antibiotics remains a public health concern and contributes to the risk of antimicrobial resistance. To raise public awareness and knowledge about appropriate antibiotic use, an educational activity was conducted during the Car Free Day event in the Sudirman area of Jakarta. The education was delivered through direct counseling using leaflet media to participants aged 15 years and above. A total of 38 individuals took part in the activity and completed questionnaires before and after the session. The results showed an increase in the average knowledge score from 51.7 to 71.4. Statistical analysis using a paired t-test indicated a significant difference (p < 0.05), suggesting that the education had a positive impact on participants’ understanding. Furthermore, it was found that some members of the public still consume antibiotics without a doctor’s prescription. This activity demonstrates that public-space educational approaches can serve as a strategic effort to improve community understanding of rational antibiotic use.